THE ROLE OF SELF-EFFICACY AND LEARNING INDEPENDENCE IN IMPROVING LEARNING OUTCOMES OF VOCATIONAL STUDENTS - Manurung, Maria; Faslah, Roni; Suherdi, (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
The purpose of this study was to determine whether there is an effect of self-efficacy and learning independence simultaneously on learning outcomes. The research method used is quantitative method with data collection techniques through distributing questionnaires. The sampling technique used was Probability Sampling, and a sample of 104 students was obtained. The research location was at SMKN 22 Jakarta. The data analysis carried out is the classical assumption test, multiple linear regression and hypothesis testing using the SPSS program. The significance test of the individual parameters of the self-efficacy variable obtained a sig. value of 0.004, and the learning independence variable obtained a value of 0.000, so it can be interpreted that there is an influence between self-efficacy and learning independence on learning outcomes partially. The results of the simultaneous test, in the Anova table obtained a significance value of 0.000. This means that the variables of self-efficacy and learning independence have a simultaneous effect on learning outcomes. This study has provided a practical contribution where students need to increase their self-confidence and independent attitude in learning, so that they are expected to obtain good learning outcomes.